Anaesthesia for Cesarean Section in a Tertiary Care Center - Shrestha, CK (Journal of Nepal Health Research Council, 2010)
Background: Cesarean section is in rising trend both in developed and developing countries. The role of appropriate choice of safest anaesthetic technique for individual patients depends upon number of factors. The study aims to find the pattern of anaesthesia used in tertiary care setting. Methods: A retrospective study using secondary data from the hospital was analyzed among total of 2044 cases from April 2005 to April 2006. Demographic profile and use of different types of anaesthetic technique were studied. Descriptive analysis was used to calculate the frequency and percentage and their relations. Results: Most patients fell on the age groups, 848 (41.48%) in 21-25 followed by 602 (25.08%) in 26-30 and 321 (15.65%) in 14-20. Out of the total 2044 cases, 1983 (97.01%).were emergency cesarean and 61 (2.98%) were elective cesarean. The top three indications for cesarean section were previous cesarean section, fetal distress and cephalopelvic disproportion. Previous cesarean section was found to be in 520 (25.4%), and Fetal distress in 434 (21.5%), and cephalopelvic disproportion in 207 (10.6%). The choice of anaesthesia among this group showed spinal 1632 (79.84%) being the preferred choice followed by general anaesthesia 402 (19.66%) and local epidural anaesthesia 10 (0.48%). Conclusions: Majority of the cesarean section are emergency. The preferred choice of anaesthesia is spinal. Previous cesarean section is the commonest indication followed by fetal distress and cephalopelvic disproportion. Key words: cesarean section; general anaesthesia; previous cesarean section; spinal anesthesia DOI: 10.3126/jnhrc.v7i2.3018 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 112-115